Wobble-board balance intervention to decrease symptoms and prevent reinjury in athletes with chronic ankle instability: An exploration case series - Wright, J.; Nauman, S. L.; Bosh, J. C. (Journal of Athletic Training, 2020)
Controlled research has shown that a single-exercise wobble-board intervention is effective at reducing symptoms and increasing function in patients with chronic ankle instability. However, the effectiveness of this protocol has not been documented in a realistic intercollegiate athletics environment. Eight intercollegiate athletes with chronic ankle instability participated in an 8-week (3 sessions/wk) wobble-board intervention. In a realistic environment, this simple intervention was feasible to implement and resulted in meaningful improvements in patient-reported stability for more than half of the patients (5 of 8) but only improved the global rating of function and pain for a minority of the patients (2 of 8 and 3 of 8, respectively). Not all patients experienced equal symptom reduction; however, no new ankle sprains occurred during the interventio